AGRARIAN STRATEGY AND POLICY OF THE REPUBLIC OF SERBIA - Ljubojević, Ratko; Blanuša, Andrija; Petrović, Slobodan (Economics of Agriculture, 2022)
The subject matter of this paper are the changes in the directions and content of the agrarian strategy and policy in the Republic of Serbia during the last two decades, which occurred primarily due to the need to adjust to the standards of the Common Agricultural Policy of the European Union. The paper starts from the assumption that the process of creating agrarian policy and its transmission to economic ﬂows is very complex and slow and requires the activity of a large number of actors and relevant institutions. Key strategic documents in the field of agriculture as well as measures of the current agricultural policy were analyzed. The aim of the paper is to examine the compliance of current agricultural policy measures with the priorities of agricultural development that are determined by these strategic documents, and above all the Strategy of Agriculture and Rural Development of the Republic of Serbia for the period 2014-2024.